Perspectivas teóricas publicadas em artigos sobre envelhecimento humano - Maraschin, Renata (2011)
The production of knowledge about the human aging process is influenced by common sense, by science, for reasons of individual, social, political, economic, biological, religious, educational, cultural and recently academic nature. The body of knowledge (product) resulting from attempts to describe or explain the reality of a culture at one time on how to think and act about old age and age. Depending on the guiding concept, the speeches and actions tend to generate different implications for the elderly, for professionals working with these groups, and society as a whole. In this sense the present study aims to identify prospects/trends in journal articles from three universities of Rio Grande do Sul relating them to the theoretical concepts explained by the authors Humberto Maturana, Fritjof Capra, Edgar Morin, António Damásio, Paulo Freire, representatives of the current that involves new paradigms. The data revealed a predominance of conceptions markedly influenced by the classic/traditional paradigm. The result from this is the understanding of the relationship among professionals, elderly and society based on in derogatory understanding of aging, with limited capacity to respond to growing calls for ethical social life that respects differences. It is possible that more elaborated theoretical approaches and next, perhaps, of what is proposed as interdisciplinarity, they are more consistent with the contemporary demands. The advancement of knowledge and its renewal through research and education is a very important condition for change of perspective in the process of training and professional intervention aiming social change. Although aware of some limitations, this paper aspired to be "one more brick" in the construction of this necessary because vital "wall" of the renewal of knowledge on the human aging